THE PERSPECTIVES OF SOUTH AFRICAN LEGAL PROFESSIONALS ON RESTORATIVE JUSTICE: AN EXPLORATIVE QUALITATIVE STUDY - Louw, Dap (Social work, 2016)
Disillusionment with especially imprisonment has led to the option of implementing restorative justice. However, restorative justice is not currently utilised to its fullest potential extent in South Africa. A possible explanation for the limited application was investigated by exploring the views that legal professionals hold about restorative justice. In order to obtain an in-depth understanding of these opinions, a qualitative research methodology was employed. It revealed a generally positive disposition by the participants towards restorative justice, although some cautionary preconditions were recommended. This exploratory finding opens the door for forensic professionals to consider this option more frequently